2021
DOI: 10.1093/jpp/rgab080
|View full text |Cite|
|
Sign up to set email alerts
|

Remimazolam alleviates neuropathic pain via regulating bradykinin receptor B1 and autophagy

Abstract: Objectives Neuropathic pain (NP) represents a broad scope of various pathological ramifications of the nervous system. Remimazolam is a proved sedative in treating neuropathic pain. Considering the Bradykinin receptor’s vital role and the potentials of Bradykinin receptor B1 (BDKRB1) in the neuropathic pain-signalling pathway, we nominated them as a primary target for remimazolam. Methods In this study, rats were injected wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…It is also not clear whether remimazolam itself has these effects; no data appear to be presented relating to remimazolam itself, although it is implied by the title of this publication. Recently, it has also been reported that remimazolam alleviates neuropathic pain via regulating the bradykinin B 1 receptor and autophagy ( Xie et al, 2021 ). Studies to examine inhibition by flumazenil and the effects of other benzodiazepines, such as midazolam, would be useful in order to determine whether this effect is mediated via the benzodiazepine site on the GABA A receptor or some other effect of remimazolam or its metabolite.…”
Section: Remimazolammentioning
confidence: 99%
“…It is also not clear whether remimazolam itself has these effects; no data appear to be presented relating to remimazolam itself, although it is implied by the title of this publication. Recently, it has also been reported that remimazolam alleviates neuropathic pain via regulating the bradykinin B 1 receptor and autophagy ( Xie et al, 2021 ). Studies to examine inhibition by flumazenil and the effects of other benzodiazepines, such as midazolam, would be useful in order to determine whether this effect is mediated via the benzodiazepine site on the GABA A receptor or some other effect of remimazolam or its metabolite.…”
Section: Remimazolammentioning
confidence: 99%
“…Through TLR4 receptor downregulation, remimazolam was shown to interfere with lipopolysaccharide (LPS)-induced endotoxemia via blockade of NF-kB signaling pathway and reversal of LPS-induced phosphorylation of Akt and Erk protein kinases essential for neuronal survival [32 ▪▪ ]. The interaction with NF-kB was also beneficial in promoting glioma cell apoptosis in vitro [33] and in alleviating neuropathic pain in adult rats [34].…”
Section: Remimazolam: a Novel Ultra-short-acting Benzodiazepinementioning
confidence: 99%
“…Autophagy is widely believed to be associated with multiple neurodegenerative diseases, and microglial activation is closely related to neuroinflammation (Plaza-Zabala et al 2017;Su et al 2016). Previous studies have reported that LPS stimulates autophagy in microglia (Qin et al 2018;Xie et al 2021). To further determine the role of autophagy in LPS-induced microglial activation, BV2 cells were treated with 3-MA (autophagy inhibitor) and LPS alone or together.…”
Section: Autophagy Can Be Involved In the Role Of Cd147 In Lps-induce...mentioning
confidence: 99%